Microstructure and Hardness Study of Al6061 Resulting from Artificial Aging - Izzatus Tsamroh, Dewi; Puspitasari, Dewi; Puspitasari, Poppy; Mustapha, Mazli (Universitas Negeri Surabaya or The State University of Surabaya, 2025)
This research aimed to improve the mechanical properties of Al6061 alloy through artificial aging heat treatment. The method used in this research was a laboratory-based experimental method. The Al6061 alloy was heated in a muffle furnace at a temperature of 480°C and held for 30 minutes. Next, rapid cooling (quenching) was carried out using cooling media of dromus oil. Then, specimens were reheated at 190°C for 2 hours, 4 hours and 6 hours for artificial aging process. The heat-treated specimens were tested for microstructure and hardness numbers. The data obtained were compared and analysed using image-J software. The research results showed that the smallest grain diameter was obtained in specimens treated with artificial aging for 4 hours, which was 47.633 µm. In this specimen, the β-Mg2Si phase was found to be 19.752 %. The highest hardness number was obtained in specimens with the same variation, which was 110.8 HRE.